HEDONISTIC BEHAVIOR BY MALE GROUP STUDENTS REFLECTED IN LONE SCHERFIG’S THE RIOT CLUB (2014) - Hayu Febriantika Rasmana (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2021)
This research is conducted to analyze the hedonistic behavior of male group students revealed in Lone Scherfig’s The Riot Club (2014) movie and the social reactions towards hedonistic behavior in The Riot Club (2014) movie. There are two problem statements in this research. First, how are hedonistic behavior by male group students revealed in The Riot Club (2014) movie? Second, how are the social reactions towards hedonistic behavior by male group students seen in The Riot Club (2014) movie? The researcher used the qualitative method to examine the problem. The theory and approaches that the researcher used is Sociology of Literature, Hedonism, and Social Class. The result of this study show that hedonistic behaviors are realized in actions and appearance, do free sex like the members do, then hangout at cafes or restaurants to have fun, and use illegal drugs such as cocaine and often drink alcohol such as vodka. Second, disappointment and rejection are forms of social reaction towards hedonistic behavior by The Riot Club.